CCL21‐expression and accumulation of CCR7+ NK cells in livers of patients with primary sclerosing cholangitis. Issue 5 (27th February 2019) - Langeneckert, Annika E.; Lunemann, Sebastian; Martrus, Glòria; Salzberger, Wilhelm; Hess, Leonard U.; Ziegler, Annerose E.; Poch, Tobias; Ravichandran, Gevitha; Matschl, Urte; Bosse, Jens B.; Tiegs, Gisa; Fischer, Lutz; et al.
Abstract: The pathogenesis of primary sclerosing cholangitis (PSC), an autoimmune liver disease, remains unknown. The aim of this study was to characterize peripheral blood and intrahepatic NK cells from patients with PSC. Peripheral blood samples from patients with PSC, other autoimmune liver diseases, and from healthy control individuals were used, as well as liver tissues from PSC patients undergoing liver transplantation. Multiparameter flow cytometry showed that peripheral blood NK cells from PSC patients were significantly enriched for CCR7 + and CXCR3 + cells, and CCR7 + but not CXCR3 + cells were also significantly increased within intrahepatic NK cells. PSC patients undergoing liver transplantation furthermore had significantly higher plasma levels of the CCR7‐ligand CCL21, and the CXCR3‐ligands CXCL10 and CXCL11, and significantly higher levels of CCL21, but not CXCL10, were detected in liver tissues. CCR7 + and CXCR3 + NK cells from PSC patients exhibited significantly higher functional capacity in peripheral blood, but not liver tissues, consistent with chronic activation of these NK cells in the inflamed liver. These data show that PSC is characterized by intrahepatic CCL21 expression and accumulation of CCR7 + NK cells in the inflamed liver tissue. Abstract : Our data suggest recruitment of CCR7 + peripheral blood NK cells into the liver associated with elevated CCL21‐expression within liver tissues of patients with PSC, and indicate that NK cells participate into the inflammatory processes that lead to the progressive destruction of bile ducts.